Optimisation as a process for understanding and managing river ecosystems. (September 2016) - Barbour, E.J.; Holz, L.; Kuczera, G.; Pollino, C.A.; Jakeman, A.J.; Loucks, D.P.
Abstract: Optimisation can assist in the management of riverine ecosystems through the exploration of multiple alternative management strategies, and the evaluation of trade-offs between conflicting objectives. In addition, it can facilitate communication and learning about the system. However, the effectiveness of optimisation in aiding decision making for ecological management is currently limited by four major challenges: identification and quantification of ecosystem objectives; representation of ecosystems in predictive simulation models; specification of objectives and management alternatives in an optimisation framework; and evaluation of model results against actual ecological outcomes. This study evaluates previous literature in ecology, optimisation and decision science, and provides a strategy for addressing the challenges identified. It highlights the need for better recognition and analysis of assumptions in optimisation modelling as part of a process that generates and shares knowledge. Highlights: Optimisation can assist in the management and understanding of complex systems. We review the use of optimisation for ecosystem management in river systems. We highlight the challenges in formulating objectives, developing models, and applying optimisation for ecosystem management. Recommendations are provided to better recognise and address these challenges. Greater consideration of assumptions and limitations is needed to better inform decision making.